Implementation of User-Centered Design (UCD) Method in Planning User Interface Application at Library Faculty of Computer Science Sriwijaya University - Halimah; Dwi Rosa Indah (INFOKUM, 2022)
The role of Information Technology in the revolution era is very important for many business activities that contribute to fundamental changes in the structure, operations, and management of organizations. This study aims to recognize the Implementation of the User-Centered Design (UCD) Method in Planning User Interface Applications in Library Faculty of the Computer Science Sriwijaya University. This research employed the User Centered Design (UCD) method with stages of planning the human-centered design process, understanding the context of use, specifying user requirements, designing solutions, and evaluating against requirements. The subjects in this study were some library visitors of the Faculty of Computer Science, Sriwijaya University, and the librarian of the Faculty of Computer Science, Sriwijaya University. The time of the study was held on September-November 30, 2022. Data collection was from interviews and questionnaires. The research was held in the library of Sriwijaya University. Research result on testing process and usability testing performed by the method of System Usability Scale (SUS) obtained a grade of 85,83 with Category A or Excellent so that the design of this application is considered feasible to be developed. User Interface is still in the form of design so it is expected, especially to the Faculty of Computer Science Sriwijaya University, to develop this design into a program.